RIB OSTEOMYELITIS: A RARE COMPLICATION OF VARICELLA - Luís,Madalena Sales (2019)
ABSTRACT Objective: To report a case of varicella complicated by acute osteomyelitis in order to remind of a rare and potentially serious complication of a very common pediatric disease. Case description: A previously healthy 3-month-old female infant with 10-day history of varicella was admitted to the hospital for fever, groan and prostration. The initial laboratorial evaluation was compatible with bacterial sepsis. By the third day after admission, a swelling of the seventh left rib had developed. The ultrasound and scintigraphy evaluation suggested rib osteomyelitis. Blood cultures were negative. The patient completed six weeks of antibiotics with favorable clinical, laboratorial and imaging evolution. Comments: Varicella is one of the most frequent exanthematic diseases of childhood and it is usually self-limited. The most frequent complication is bacterial infection of cutaneous lesions. Osteoarticular complications are rare, and rib osteomyelitis is described in less than 1% of cases. The main route of dissemination is hematogenic, and the most frequent etiological agent is Staphylococcus aureus. The prognosis is generally good and depends on early detection and antibiotic initiation.